2020
DOI: 10.1039/d0ra02587a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the electron energy structure of TiO2(B) and anatase photocatalysts through analysis of electron trap density

Abstract: The electron energy structures of TiO2(B) and anatase were estimated by analyzing the energy-resolved distribution of electron traps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…66,67 Taking into consideration of the band gap of 3.22 eV for anatase nanoparticles (Figure S12, Supporting Information), the so-called type-II configuration could be presented for the as-transformed TiO 2 (B)/anatase heterophase junction based on the band positions of the TiO 2 (B) nanosheets and anatase nanoparticles (Figure 7a). 68,69 Such a heterojunction type was further confirmed by photodeposition of Pt nanoparticles to monitor the electron flow direction within the heterophase junction. 70,71 It can be seen that the Pt nanoparticles are anchored around TiO 2 (B) nanosheets rather than staying randomly on the anatase part, suggesting that the photogenerated electrons tend to reside on the TiO 2 (B) part as indicated by the type-II route (Figure S13, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…66,67 Taking into consideration of the band gap of 3.22 eV for anatase nanoparticles (Figure S12, Supporting Information), the so-called type-II configuration could be presented for the as-transformed TiO 2 (B)/anatase heterophase junction based on the band positions of the TiO 2 (B) nanosheets and anatase nanoparticles (Figure 7a). 68,69 Such a heterojunction type was further confirmed by photodeposition of Pt nanoparticles to monitor the electron flow direction within the heterophase junction. 70,71 It can be seen that the Pt nanoparticles are anchored around TiO 2 (B) nanosheets rather than staying randomly on the anatase part, suggesting that the photogenerated electrons tend to reside on the TiO 2 (B) part as indicated by the type-II route (Figure S13, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…This can be rationalized by considering that a well-defined phase junction forms between TiO 2 (B) and anatase TiO 2 . , Further analysis of the band structure of the TiO 2 (B) nanosheet precursor from the Tauc plot determines a band gap of about 3.36 eV (Figure S11, Supporting Information), which is wider than that of the commonly reported TiO 2 (B) materials (3.00-3.20 eV). This is probably due to the quantum size effect that semiconductor nanoparticles with a smaller particle size usually exhibit a wider band gap. , Taking into consideration of the band gap of 3.22 eV for anatase nanoparticles (Figure S12, Supporting Information), the so-called type-II configuration could be presented for the as-transformed TiO 2 (B)/anatase heterophase junction based on the band positions of the TiO 2 (B) nanosheets and anatase nanoparticles (Figure a). , Such a heterojunction type was further confirmed by photodeposition of Pt nanoparticles to monitor the electron flow direction within the heterophase junction. , It can be seen that the Pt nanoparticles are anchored around TiO 2 (B) nanosheets rather than staying randomly on the anatase part, suggesting that the photogenerated electrons tend to reside on the TiO 2 (B) part as indicated by the type-II route (Figure S13, Supporting Information). Thereby, the photoinduced electrons on the side of anatase tend to migrate to TiO 2 (B) and holes on the side of TiO 2 (B) transfer reversely to anatase, boosting the charge separation and photoreactivity of the heterophase junction.…”
Section: Resultsmentioning
confidence: 85%
“…The superior performance of our method can be attributed to the large surface area and enhanced separation of photogenerated charges induced by the anatase/TiO 2 (B) heterojunction. In our previous work, the electron energy structure of anatase/TiO 2 (B) nanotubes was suggested using the energy-resolved distribution of electron traps (ERDT) of TiO 2 (B), anatase, and a 1:1 mixture of anatase and TiO 2 (B) measured by reversed double-beam photoacoustic spectroscopy. These results revealed that electron-transfer excitation to the electron traps of TiO 2 (B) occurs based on the high density of states in the valence band of anatase. Furthermore, the valence band top (VBT) of TiO 2 (B) is located at a deeper energy level (approximately 0.7 eV) than the VBT of anatase in the mixture, and the ERDT patterns of the anatase/TiO 2 (B) nanotubes in the mixture match.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, silver particles or copper particles deposited on P25 as a cocatalyst were used to decompose low concentrations of H 2 S. Although improved activity was observed, complete treatment was not achieved . In our previous work, we focused on anatase/TiO 2 (B) nanotubes which were found to be more photocatalytically active than P25 owing to a large surface area and efficient interfacial charge transfer. , TiO 2 (B) is a widely studied monoclinic metastable phase that has attracted attention as a photocatalytically active TiO 2 phase. Therefore, in this study, we applied anatase/TiO 2 (B) nanotubes to the gas-phase decomposition of H 2 S and succeeded in decomposing H 2 S to 1 ppb or less, which are concentrations that do not cause odor problems.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that TiO 2 (B) exhibited a slower recombination rate of photogenerated carriers than TiO 2 (A). In addition, the formation of TiO 2 (B)/TiO 2 (A) homogeneous heterojunctions further boosted the photogenerated charge separation because of the small built-in potential [ 25 , 27 ], leading to the substantially increased photocurrent shown in Figure 6 a. Figure 6 b shows the electrochemical impedance plots of the raw TiO 2 , DT-200, and DT-180.…”
Section: Resultsmentioning
confidence: 99%